Perkaitan Di Antara Amalan Pengurusan Masa Pentadbir Dengan Iklim Sekolah Di Daerah Padang Terap Pendang, Dari Persepsi Guru-Guru - Ghazali, Ariffin (1997)
The purpose of this study is to determine the time management practices among the school administrators, i.e the principals and the headmasters, and it relationship with the school climate, from the teachers’ perceptions, in the District of Padang Terap Pendang, Kedah, Kedah Darul Aman. The respondents of this study were 180 teachers from the 20 elementary and secondary schools. Five variables used in this study were: Time management, school climate, gender of the administrators, grade of school, category of school ( elementary and secondary ) and years of administrators experience. The time management practices by the administrators, from teachers’ perceptions was studied by Executive Time Management Tnstrument (ETML), developed by Distasio (1985) but with some modification. In order to assess the school climate, the Climate Profile Questioner (CPQ) ( CFK Ltd, 1974), was used. Nine hypotheses were developed and tested using correlation, t-test, and one way- ANOVA analyses. Hypothesis 1 was tested through use of Pearson Product- Moment correlation procedures, while hypotheses 2 through 9 was tested through t-test and one way - ANOVA. All hypotheses were examined at the 05 level of significance. The findings of this study indicate that : (1) there was a significant relationship between time management practices by the administrators with the school climate (r = 0.65; p < .0l). The time management practices by the administrators were classified as sometimes to nearly always, while the schools climate was positive. (2) There were no significant differences existed between time management practices by the administrators and the gender of the administrators, grade of school, category of school and years of administrators experiences. (3) There were also, no significant differences existed between school climate and the gender of the administrators, grade of school, category of school and years of administrators experiences. The implication of this study suggested that the schools administrators should be exposed and practise in the area of time management as frequently as possible, in order to create a positive school climate and effective school. Recomendations for future research were specified.